Calcium sensing receptor regulate claudin-14 via PKA-STAT3 pathway in rat model of nephrolithiasis - Luo, Peiyue; Chen, Tao; Zheng, Liying; Zou, Junrong; Zou, Jun; Li, Wei; Chen, Qi; Cheng, Le; Qian, Biao (Frontiers in Pharmacology, 2024)
The calcium-sensitive receptor (CaSR) has been identified as a key factor in the formation of kidney stones. A substantial body of research has illuminated the function of CaSR in stone formation with respect to oxidative stress, epithelial injury, crystal adhesion, and stone-associated proteins. Nevertheless, as a pivotal molecule in renal calcium excretion, its pathway that contributes to stone formation by regulating calcium supersaturation remains underexplored. Available evidence indicates that CaSR plays a significant role in calcium imbalance diseases through epigenetic regulation of claudin-14 levels. In this study, we demonstrate that activated CaSR affects claudin-14 expression by directly regulating the phosphorylation level of signal transducer and activator of transcription 3 (STAT3) and is closely associated with ethylene glycol-induced renal stone formation. In vitro and in vivo observations revealed that calcium oxalate induces high expression of CaSR-claudin-14. Specifically, CaSR regulates claudin-14 expression through phosphorylation modification of STAT3 via protein kinase A (PKA). In vitro, the intervention of PKA and STAT3 reversed the elevated claudin-14 levels and stone formation induced by CaSR.Finally, we generated cldn-14 knockout rats using CRISPR-Cas9 technology and observed that ethylene glycol still induced stone formation in these animals. Nevertheless, the specific activation or inhibition of CaSR demonstrated no notable impact on stone formation. In conclusion, the results of our study indicate that calcium oxalate crystals induce the activation of the pro-stone pathway of CaSR. That is, activated CaSR regulates claudin-14 levels via the PKA-STAT3 pathway, which further promotes calcium salt stone formation. The role of CaSR in the regulation of stone homeostasis is further enriched.